Income Convergence and Divergence in European Regions: Insights and Policy Implications - Saglam, Yagmur; Önkan, Özge (Panoeconomicus, 2025)
The allocation of wealth in society has been a fundamental question and challenge in economics. Concentrating most wealth in a small segment of society while leaving the rest with a smaller portion can lead to income inequality and social issues. Income inequality varies across cultures, historical periods, economic structures, and economic systems. Our study tests and analyzes comparative income convergence in Eastern Europe, Western Europe, Central Europe, and the Baltic regions. It is important to note that our model is region-specific rather than country-specific. Our study asserts that income levels converge at an average level and within states, promoting income distribution convergence. The analysis was conducted to examine stochastic convergence in Europe within the panel stationarity (Fourier KPSS) test, revealing that regional economic inequalities in Europe are likely to either persist or even widen. JEL: C23, D31, O18, H20